2017
DOI: 10.1371/journal.pone.0185868
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous assessment of iodine, iron, vitamin A, malarial antigenemia, and inflammation status biomarkers via a multiplex immunoassay method on a population of pregnant women from Niger

Abstract: Deficiencies of vitamin A, iron, and iodine are major public health concerns in many low- and middle-income countries, but information on their status in populations is often lacking due to high costs and logistical challenges associated with assessing micronutrient status. Accurate, user-friendly, and low-cost analytical tools are needed to allow large-scale population surveys on micronutrient status. We present the expansion of a 7-plex protein microarray tool for the simultaneous measurement of up to seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 53 publications
6
58
2
Order By: Relevance
“…The financial inaccessibility of nutritious foods during pregnancy and gender norms related to household food procurement have been reported extensively in low‐ and middle‐income countries (Christian et al, ; Girard, Dzingina, Akogun, Mason, & McFarland, ; Hartini, Padmawati, Lindholm, Surjono, & Winkvist, ; Huybregts, Roberfroid, Kolsteren, & Van Camp, ; Levay, Mumtaz, Rashid, & Willows, ; Scorgie et al, ). However, documenting the impact of these social and market forces on nutritional and pregnancy outcomes has been less of a priority for research conducted in Niger, where studies measuring maternal micronutrient deficiency burdens and other pregnancy‐related outcomes dominate the current research agenda (Brindle et al, ; Kay, Idrissa, & Hampton, ; Seim et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The financial inaccessibility of nutritious foods during pregnancy and gender norms related to household food procurement have been reported extensively in low‐ and middle‐income countries (Christian et al, ; Girard, Dzingina, Akogun, Mason, & McFarland, ; Hartini, Padmawati, Lindholm, Surjono, & Winkvist, ; Huybregts, Roberfroid, Kolsteren, & Van Camp, ; Levay, Mumtaz, Rashid, & Willows, ; Scorgie et al, ). However, documenting the impact of these social and market forces on nutritional and pregnancy outcomes has been less of a priority for research conducted in Niger, where studies measuring maternal micronutrient deficiency burdens and other pregnancy‐related outcomes dominate the current research agenda (Brindle et al, ; Kay, Idrissa, & Hampton, ; Seim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Women described specific symptoms associated with morning sickness as constraints to a healthy prenatal diet, but these symptoms typically resulted in aversions to food overall, rather than to specific food items -as documented in other studies (Young & Pike, 2012 et al, 2015). However, documenting the impact of these social and market forces on nutritional and pregnancy outcomes has been less of a priority for research conducted in Niger, where studies measuring maternal micronutrient deficiency burdens and other pregnancy-related outcomes dominate the current research agenda (Brindle et al, 2017;Kay, Idrissa, & Hampton, 2014;Seim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The observed lack of concordance may be attributed to the sample preparation. In 2017, the Quansys assay was validated using a Nigerian cohort of heparinized plasma samples [ 15 ]. The fact that serum and capillary samples were used in this study could account for some of the observed assay differences.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of this study was the assessment of iron status by measuring two different biomarkers (ferritin and sTfR) using a validated method [29]. However, we do acknowledge that a recent study comparing the Quansys multiplex immunoassay with reference-type assays found poor precision for sTfR in comparison with the Roche cobas 6000 clinical analyser [41].…”
Section: Discussionmentioning
confidence: 98%
“…Plasma was separated within 1 h after blood collection, and aliquots stored at −20 • C for a maximum of 14 days until transportation (on dry ice) for storage at −80 • C until analysis. For the analysis of iron status indices and the inflammation/infection markers C-reactive protein (CRP) and alpha-1-acid glycoprotein (AGP), the Q-Plex™ Human Micronutrient Array (7-plex, Quansys Bioscience, Logan, UT, USA) was used [29].…”
Section: Biomarker Analysismentioning
confidence: 99%